2018
DOI: 10.1007/s11136-018-1851-2
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of measurement equivalence study findings of the SF-36® and SF-12® Health Surveys across electronic modes compared to paper administration

Abstract: PurposePatient-reported outcome (PRO) measures originally developed for paper administration are increasingly being administered electronically in clinical trials and other health research studies. Three published meta-analyses of measurement equivalence among paper and electronic modes aggregated findings across hundreds of PROs, but there has not been a similar meta-analysis that addresses a single PRO, partly because there are not enough published measurement equivalence studies using the same PRO. Because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 36 publications
1
34
3
2
Order By: Relevance
“…Unlike previous research [35,[37][38][39], we found the domains of BP and SF in general had poor discrimination of items, while PF in general, as well as BP, SF, RP, and VT on the SF-12, had higher discriminations of items than in SF-36. We suggest that, compared with PF items, the items in these other domains were not easy for teenagers to understand, resulting in a lack of sensitivity in the measurement.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike previous research [35,[37][38][39], we found the domains of BP and SF in general had poor discrimination of items, while PF in general, as well as BP, SF, RP, and VT on the SF-12, had higher discriminations of items than in SF-36. We suggest that, compared with PF items, the items in these other domains were not easy for teenagers to understand, resulting in a lack of sensitivity in the measurement.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, it may also be attributed to the presence of inconsistent responses, which might occur if respondents completed a questionnaire without comprehending the items, which might occur with adolescents [21]. Due to the brevity of the SF-12 instrument, related research has shown that it is not possible to get reliable information for each of the eight domains, so that one would not be able to draw conclusions about speci c domains [37]. Indeed, we found the SF-36 was better than the SF-12 in terms of reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies generally showed good concordance between the electronic and paper versions of various questionnaires across a wide variety of diseases and conditions, [25][26][27] but those studies were not controlled clinical trials, they did not use smartphone electronic versions, and did not include scales used in depression. Nevertheless, the results of the present study for QIDS-SR16 and PHQ-9 are consistent between the paper and electronic versions, as supported by the previous studies mentioned above.…”
Section: Consistency Between Electronic and Paper Versionsmentioning
confidence: 99%
“…Data collection was carried out during class intervals or after classes in online and offline forms. The different forms of the questionnaire, either online or paper-based, had little impact on the equivalence of our study [15]. Students' participation was voluntary, and the survey was anonymised.…”
Section: Measures and Proceduresmentioning
confidence: 99%